ROAD TRANSPORT DECARBONIZATION, TOURIST MOBILITY, AND SUSTAINABLE TOURISM: AN INTEGRATED REVIEW WITH POLICY IMPLICATIONS FOR INDONESIA - Siti Hadidjah; Sugeng Budiharsono Budiharsono (Jurnal Pariwisata Tawangmangu, 2026)
The increasing urgency of climate change has driven attention toward transport decarbonization and sustainable mobility as vital components of sustainable tourism development. However, studies comprehensively integrating these three aspects remain limited. This study aims to synthesize the relationships among land transport decarbonization, tourist mobility, and sustainable tourism development, with a focus on policy implications for Indonesia. Using a Systematic Literature Review (SLR) guided by the PRISMA framework, data from 61 Scopus-indexed articles were analyzed through thematic synthesis. The findings identify five main themes: (1) sustainable mobility and transport decarbonization, (2) tourist mobility and accessibility, (3) public transport and destination connectivity, (4) sustainable tourism outcomes, and (5) policy and governance. Transport decarbonization influences sustainable tourism primarily through changes in tourist mobility and accessibility. Tourist mobility serves as the primary bridge between transport interventions and sustainability outcomes. This study proposes an integrated conceptual framework that positions decarbonization as a driver of sustainable tourism. For Indonesia, the implications underscore the need to improve public transport, strengthen destination connectivity, and integrate transport and tourism policies to support low-carbon tourism.